2017
DOI: 10.5811/westjem.2016.10.32233
|View full text |Cite
|
Sign up to set email alerts
|

Who to Interview? Low Adherence by U.S. Medical Schools to Medical Student Performance Evaluation Format Makes Resident Selection Difficult

Abstract: IntroductionThe Medical Student Performance Evaluation (MSPE) appendices provide a program director with comparative performance for a student’s academic and professional attributes, but they are frequently absent or incomplete.MethodsWe reviewed MSPEs from applicants to our emergency medicine residency program from 134 of 136 (99%) U.S. allopathic medical schools, over two application cycles (2012–13, 2014–15). We determined the degree of compliance with each of the five recommended MSPE appendices.ResultsOnl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…In terms of the structure of the MSPE, end-users indicated that the noteworthy characteristics were not highly valued with approximately one-third of readers citing it as very or extremely influential. The identification of noteworthy characteristics is sometimes stressful for students, onerous for the MSPE writers, open to implicit bias, and not sufficiently consistent to allow for comparisons of students across schools [ 15 ]. The information provided in noteworthy characteristics is available in other components of the application for those who advocate its usefulness as part of a holistic review of applicants [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the structure of the MSPE, end-users indicated that the noteworthy characteristics were not highly valued with approximately one-third of readers citing it as very or extremely influential. The identification of noteworthy characteristics is sometimes stressful for students, onerous for the MSPE writers, open to implicit bias, and not sufficiently consistent to allow for comparisons of students across schools [ 15 ]. The information provided in noteworthy characteristics is available in other components of the application for those who advocate its usefulness as part of a holistic review of applicants [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Until this issue is addressed, it is likely that residency programs will place greater importance on other objective measures (e.g., USMLE Step 2 CK scores, NBME subject exam scores) or on their own internally generated information, such as the EM’s standard letter of evaluation (SLOE) [ 27 , 28 ]. Some of this mistrust may be mitigated with MSPEs that offer more objective information via useful transparent communication about a student’s professionalism, comparative performance indicators such as class rank, and honesty about academic progress, ideally in the body of the MSPE, not in appendices, which require additional searching and scrolling [ 11 , 15 ]. To maximize benefit to the end-user, the medical education community must strive for greater standardization of this document to promote focus on student performance rather than spending unnecessary time deciphering each school’s unique approach.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of this RCT will be performed by intent-to-treat (ITT) principle, including all randomized participants 56…”
Section: Introductionmentioning
confidence: 99%
“…78,82,86 MSPE: Twelve articles proposed requiring objective data in the MSPE, particularly class rank, c l e r k s h i p g r a d e s , a n d s h e l f e x a m i n a t i o n scores. 4,11,12,18,31,39,59,[91][92][93][94][95] Proponents also sought disclosure of professionalism issues, academic difficulties, and leaves of absence. Additionally, 8 articles endorsed standardization of the MSPE structure, content, and language.…”
Section: Reforms To the Application Review Processmentioning
confidence: 99%